A balatoni turizmus változásai az elmúlt három évtizedben - Wilhelm, Réka (Közép-Európai Közlemények, 2024)
Lake Balaton is the largest lake in Central Europe, with a length of 77 km and an average width of 7.7 km. After Budapest, it is the second most popular tourist destination in Hungary, with a particular increase in visitors during the summer months. The development of tourism at Lake Balaton began in the 1880s, when a few landlords recognised the economic and cultural importance of tourism and started to develop infrastructure. This development process has been interrupted to a certain extent, but is still continuing today. Over 140 years, a number of mediumsized towns have grown up from the small villages of the past. Today’s Balaton Region includes 177 settlements, 44 of which are located directly on the shore. Lake Balaton is also a symbol. In some periods it has become a distinctive centre of Hungarian human culture, with high-quality works by painters, writers and poets associated with the lake and the landscape around it. However, the Balaton Region has changed a lot since the end of socialism. The emergence of a market economy, rising incomes, the emergence of private and foreign capital and the use of EU funds have brought huge changes to the life of the region. Today, Lake Balaton is still an attractive destination for the domestic holidaymaking masses. Therefore, it is worth examining the changes that have taken place in the Balaton Region in the almost 30 years since the political regime change, how the former culture of mass tourism has been transformed, and what opportunities and at the same time what difficulties this region has. My intention is to show what measures have been taken to improve and develop the natural and built environment of the destination since the regime change. Furthermore, I would like to give an overall picture of the changes in the population and tourism demand in the area.